Thoughts on the use of splinted versus single crowns - Márta Radnai; István Gorzó (Hungarian Dental Association, 2019)
There are many cases when a dentist has to decide to prepare single crowns or to connect the abutment teeth. When missing teeth have to be replaced with fixed bridges there is no choice, abutment teeth must be connected. However teeth should be connected based only on careful consideration, because the crowns casted in one piece may decrease the interdental embrasure space and compress the interdental papilla. Therefore the periodontal aspects of crown preparation must be followed. During planning, tooth preparation, impression taking, model and crown preparation, and also during cementation the embrasure area must be respected and the proximal surfaces of the crowns has to imitate the original tooth morphology, and provide access for cleaning for the patient. Otherwise patients cannot clean the proximal surfeces of the neighbouring crowns and gingivitis, periodontitis may develop. The article summarises the problems of primary splinting and the guidelines to be kept in cases when two neigbouring teeth must be connected by crowns.